Дизайн інтерʼєру арт-кафе "Меланж" в ЖК Містечко Підзамче - Вежа у м. Львові, вул. Б.Хмельницького, 207 - Іванова, Анастасія Романівна; Ivanova, Anastasiia Romanivna (Національний університет "Львівська політехніка", 2024)
Бакалаврська робота на тему «Дизайн інтер’єру арт–кафе “Меланж” в ЖК “Містечко Підзамче – Вежа” у м. Львові» присвячена розробці проєктної пропозиції інтер’єру арт-простору, який поєднує в собі функції кафе та платформи для творчої взаємодії. Основною ідеєю проєкту є створення мультифункціонального середовища, що сприяє розвитку культури, комунікації та естетичного досвіду в урбаністичному просторі. Авторське поєднання сучасних дизайнерських підходів, елементів локального мистецтва та принципів універсального дизайну дозволило створити комфортний і водночас візуально насичений інтер’єр. Для досягнення мети, в першому розділі було проаналізовано особливості функціонування арт-кафе як соціокультурного явища. Розглянуто приклади українських та зарубіжних арт-просторів, зокрема закладів, які поєднують гастрономію з мистецтвом. У другому розділі проаналізовано нормативні вимоги до організації громадського інтер’єру, принципи ергономіки, зонування, інклюзивності, а також тенденції оформлення креативних просторів. Окреслено методи експозиційної організації та принципи візуальної навігації в закладах гібридного типу. Творча частина роботи, представлена в третьому розділі, присвячена безпосередній розробці інтер’єру арт–кафе «Меланж» з урахуванням стилістичної концепції, функціонального зонування, підбору матеріалів, колористики та композиційного вирішення простору. Особливу увагу приділено художньому образу інтер’єру, який відображає відкритість до творчості та мистецького діалогу. У четвертому розділі розроблено економічну частину, зокрема складено попередній кошторис витрат на реалізацію проєкту з урахуванням матеріалів, обладнання та оздоблювальних робіт.

The bachelor’s thesis titled “Interior Design of the Art Cafe ‘Melange’ in the Residential Complex ‘Mistechko Pidzamche – Vezha’ in Lviv” is devoted to the development of a conceptual interior design proposal for an art space that combines the functions of a cafe and a platform for creative interaction. The main idea of the project is to create a multifunctional environment that promotes cultural development, communication, and aesthetic experience within an urban setting. The author’s integration of contemporary design approaches, elements of local art, and the principles of universal design made it possible to develop a comfortable, inclusive, and visually engaging interior that supports various social and creative functions. The space is designed to flexibly transition from a morning cafe to a venue for art exhibitions, cultural events, and public gatherings, thus enhancing its functionality and relevance to a diverse audience. To achieve the outlined objectives, the first chapter provides an analytical overview of art cafes as socio-cultural phenomena. It examines both domestic and international examples of art spaces that combine gastronomy with art as a strategy to foster creative atmospheres and establish points of cultural contact within urban communities. This analysis lays the foundation for developing a culturally relevant and socially responsive interior. The second chapter explores legal and regulatory frameworks governing public interior spaces, including national building codes and accessibility standards. It analyzes the key principles of ergonomics, spatial zoning, and inclusive design, as well as contemporary approaches to organizing creative, hybrid spaces. In particular, this section addresses the importance of visual communication and exhibition design as essential tools for shaping the user’s spatial experience. The third chapter, which constitutes the creative component of the thesis, focuses on the direct development of the interior design of the art cafe “Melange.” The project presents a comprehensive concept that integrates compositional, stylistic, and functional solutions. Special attention is given to the color palette, materials, lighting, and decorative elements that support the emotional and sensory experience of the visitors. The artistic identity of the cafe is articulated through flexible exhibition areas, curated visual accents, and an overall atmosphere of openness to creativity and cultural exchange. Additionally, the design prioritizes emotional and psychological comfort. Acoustic planning, textural contrast, natural and artificial lighting schemes, and zoning strategy were carefully selected to encourage both relaxation and engagement. The cafe includes secluded zones for individual visitors as well as open-plan areas for group interaction, workshops, and artistic performances. The interior also embodies sustainability principles by using eco-conscious materials and modular furniture systems. Environmentally responsible design strategies enhance both the aesthetic and functional durability of the space. A branding system integrated into the interior elements reinforces the cafe`s cultural image and strengthens its visual identity within the residential complex. The fourth chapter presents the economic component of the project. It includes a preliminary cost estimate for implementation, a selection of finishing materials, equipment, and furniture, as well as an assessment of budget efficiency and long-term maintenance. The proposed solutions aim to balance visual appeal, functionality, and affordability. As a result, the project delivers a well-grounded and detailed interior design concept for a multifunctional art cafe that not only meets the needs of food service operations but also acts as a cultural and social hub within the newly developed urban district.
Interior design of the art cafe "Melange" in the Mistechko Pidzamche - Vezha Residential Complex in Lviv, 207 B. Khmelnytskoho St.
Keywords: 6.022.03.03; арт–кафе; дизайн інтер’єру; культурний простір; інклюзивність; функціональне зонування; візуальна експозиція; урбаністичний контекст; art cafe; interior design; cultural space; inclusivity; functional zoning; visual exposition; urban context